ANALISIS YURIDIS TERHADAP LEGALITAS SUATU SURAT KEPUTUSAN PEMBERHENTIAN PEGAWAI NEGERI SIPIL OLEH BUPATI KABUPATEN MALUKU TENGGARA BARAT - Selfianus Laritmas; Yohanis Laritmas (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2019)
The State Civil Apparatus hereinafter abbreviated (ASN) is the profession of Civil Servants who are subsequently written (PNS), Provisions regarding the dismissal of Civil Servants are regulated in Law Number 5 of 2014 concerning State Civil Apparatus then written Law No. 5/2014. Matters that are reasons for dismissal of civil servants in article 87 paragraph 1 (one), paragraph 2 (two) and paragraph 4 (four) are civil servants honorably dismissed because: a. Dies; b. at own request; c. reaching retirement age; d. organizational downsizing or government policies that result in early retirement or e. incompetent physically and / spiritually so that they cannot carry out their duties and obligations, paragraph 2 (two) civil servants can be dismissed because they are sentenced to imprisonment based on court decisions that have permanent legal force for committing criminal acts with imprisonment, paragraph 4 (four) commit fraud against Pancasila and the 1945 Constitution of the Republic of Indonesia, b. sentenced to imprisonment or confinement based on a court decision that has permanent legal force because of committing a crime of occupational crime or a criminal offense related to position and / or general criminal offenses. However, the case that occurred in West Southeast Maluku Regency was subsequently written (MTB) Dismissal of Civil Servants for having similar Employee Numbers with other Employees through West Southeast Maluku Regent Decree Number 884-536 of 2014, in the case of dismissal of civil servants this does not have legality or validity , because the dismissal of civil servants must be in accordance with the above article, but the dismissal of civil servants through the MTB Regent Decree Number 884-536 of 2014 is not regulated in Law No. 5/2014.